Pengaruh Perubahan Bunga Kredit KUR Terhadap Minat Pengajuan Pada Bank Sulselbar KCP Antang - Muliana Mustafa; Karmilah Karmilah (Program Studi Administrasi Fiskal, 2025)
ABSTRACT This study aims to analyze the effect of the interest rate of People's Business Credit (KUR) on the interest in submitting a loan at Bank Sulselbar KCP Antang. The main problem raised regarding the different interest rates affecting the choice of debtors in continuing to take KUR credit. This study uses a quantitative approach with primary data from questionnaires, as well as secondary data from related documents. This study found that in the hypothesis test, the significance value was 0.003 with a standard beta coefficient value of 0.378. The results of this study indicate that the interest rate significantly affects the interest in submitting a loan with a t-count value of 3.133 <2.001. The lower the credit interest rate, the more people will apply for loans. Conversely, when interest rates increase, loan demand will usually decrease. The mechanism for changing KUR credit interest in implementing a tiered interest system is between 6% and 9%. However, debtors' perceptions of changes in KUR credit interest have different impacts on debtors. It is important for banks to recognize this variation so that they can change their policies, such as providing financial training or offering more flexible payment options.